Intergroup relations between French and migrants of francopone sub-Saharan Africa - (:unkn) unknown (My University, 2016)
The aim of this research is to update the identity changes and inter-categorical relational processes between Blacks and Whites, between Africans and Europeans on African migrants in Burgundy. We propose to understand migration as a process considering two elements: a) the temporality of the process and b) the space in which the various stages of migration take place. Our theoretical background is based on two major currents. The first one is the meta-theory of social identity, completed by the model of social partitions. The second one concerns some achievements of acculturation studies. A twofold methodology was used: firstly, the use of quantitative questionnaires, including the RepMut tool (diagnostic tool of inter-categorical relations) allowed us to highlight the underlying relations of psychological functioning mechanisms between Whites and Blacks, Natives and Migrants in our sample. Also, Interviews were carried out in order to complement and particularize the identified process with qualitative data and examples. The results allow us to consider the migration process as a multiple, variable and multidirectional phenomenon, on two axes: the geographic axis (return to the home country; migrate to a third country, or remain in the host country) and the time axis (now, in x time, after, one day, never). In the discussion a) The notions of family and African solidarity are further developed, b) the difference between the real and ideal plan are questioned in order to qualify the border between these two plans and c) the weight of multiple affiliations associated with multiple categorizations which can create an effect of "double jeopardy" are examined.
Keywords: African Research